Предметное поле социологии окружающей среды - Стегний, А. (Социология: теория, методы, маркетинг, 2008)
Substantially analyzing the notions of “social ecology” and “environmental sociology” interpreted by their adherents, the author concludes about a nearly complete terminological parallelism in a sociological approach to the study of societal-environmental interactions. In addition, considerable attention is paid to the theoretical discourse of environmental sociology and classification of the present-day investigations in the sphere of social ecology with regard to an inter disciplinary status of this branch of sociological knowledge.